Sustainable Urban spatial resilience in improving the quality of livable Green Open Space (GOS). Case study: An implementation of Green City Development Program (GCDP) in Malang City Center Development Area, Indonesia - Wikantiyoso, R; Suhartono, T; Triyosoputri, E; Sulaksono, A G (IOP conference series. Earth and environmental science, 2021)
Sustainable Development Goals are collective agreements that generally result in harmonious and sustainable development. Harmony contains understanding related to ecological, humanities, and economic aspects. Sustainable development aims to improve the quality of life of present and future generations. In other words, sustainable city development leads to the creation of livable city ecosystems. A livable city is an ideal condition that can provide space for city life in a natural and sustainable urban area. The GOS revitalization must pay attention to the dimensions of scale, structure, shape, function, and urban spatial networks. Urban Resilience as a process can interpret as an effort to increase the ability to absorb and respond to the effects of disasters and reorganize to overcome disruptions in achieving normal conditions after disaster stress or urban changes. This discussion aims to create a sustainable urban spatial resilience model in improving the quality of livable GOS. The research method used is descriptive exploratory based on GOS map data and filed survey of GOS improving implementation in the Central Malang Development Area. Analysis of spatial structure resilience and spatial accessibility was carried out to assess the convenience of using public spaces. This analysis is conducted to answer the question of what factors affect the sustainability of resilience urban Green Open Space.